AVOIDING UNPLANNED HOSPITAL ADMISSIONS IN PATIENTS WITH NEUROMUSCULAR DISEASES: A REGIONAL COLLABORATIVE AUDIT OF HOSPITAL ADMISSIONS. (29th November 2012) - Jaffer, F; Reilly, MM; Quinlivan, RR; Muntoni, F; Orrell, R; Wraige, E; Saha, R; Radunovic, A; Mummery, C; Parton, M; Hanna, M
Abstract : Background: Neuromuscular diseases require long-term multi-disciplinary care. In 2010, there were 5368 unplanned admissions for metabolic and neuromuscular conditions in England (Hospital Episodes Statistics 2007–2008). Unplanned admissions are those that occur at short notice and when there is a perceived need for clinical care (Department of Health). However, some unplanned admissions may be preventable through integrated care pathways. Preventing such admissions would reduce NHS costs, and improve quality of life for the patients. Aims and objectives: The aims of the audit were to determine the proportion of unplanned admissions, the nature of events leading to an unplanned admission, and if and admission was deemed to be preventable, what measures could be taken to avoid these. Methods: A retrospective case note audit of unplanned admissions was conducted in eight trusts across four Specialised Commissioning Groups between 2009 and 11. Neuromuscular and metabolic ICD-10 codes were used to identify patients with an unplanned admission. In the absence of national standards, consensus criteria for a potentially preventable admission were developed by an expert group of neuromuscular consultants. These included: diagnoses directly attributable to or complications of a neuromuscular disease, documentation of emergency plans, whether there was contact with healthcare professionals prior to admission and re-admissions. Results: There were 266 unplanned admissions for 200 patients. 68% were in patients with an established neuromuscular condition (of which 59.7% were directly attributable to this).42.1% of all admissions were potentially avoidable, 53% unavoidable and a decision not made in 4.9%.72.4% of admissions were in patients with established diagnosis and unknown to a specialist neuromuscular service (55% potentially avoidable).7.2% of patients with established diagnosis had emergency plans.Delayed access to a specialist, lack of disease monitoring, emergency plans and provision of equipment were factors leading to admission. Conclusions and further work: 42.1% of unplanned admissions were deemed to be preventable of which a significant proportion were directly attributable to neuromuscular disease. Less than one-third of patients with a neuromuscular diagnosis were known to a specialist neuromuscular service. Results of a total of 576 admissions from twelve participating NHS trusts will be presented to the All Party Parliamentary Group for Muscular Dystrophy in June 2012 with the recommendations from this meeting to be announced thereafter.